Formulation and Evaluation of Oro-Sustained Release Insitu Gelling Sol Using Xanthan Gum - S.SANGEETHA; HARISH.G; MALAY.K.SAMANTA (International Journal of Pharma and Bio Sciences, 2010)
The purpose of this study was to evaluate the prospective of the oral sustained delivery of xanthan gum formulation with insitu gelling properties. Xanthan gum insitu gelling sols were prepared in three different concentrations such as 0.1, 0.15, and 0.2 %( w/v) by adding bentonite as complexing agent at 0.5% (w/v). The formulated insitu gelling sols were evaluated for rheological studies and drug content. The invitro release study was performed in acidic medium followed by basic medium for about 8hrs. The bioavailability of salbutamol from the gels formed insitu in the stomach of rabbits following oral administration of the liquid formulation had the ability to sustain the drug release over a period of 6 hours.